The Sufistic Character Education according to Ibn ‘Aṭāillāh al-Sakandarī and It’s Implementation in Educational Institution in Indonesia to Spread Prace in the World: An Analytical Study on al-Ḥikam al-‘Aṭāiyyah - Mohammad Alek Mahya Shofa & Mudzakkir Ali (Pascasarjana Universitas Wahid hasyim Semarang, 2015)
Indonesia is now facing various problems such as moral degradation, corruption, deceitfulness in schools and juvenile delinquency behavior. All of these require a solution. Most education experts argue that the Sufi-style education is one of ways to solve the moral problem. Among them is Ibn Aṭāillāh al- Sakandarī who undeniably has a significant role in this field especially through his famous work, al-Ḥikam. This article tries to uncover how the role of his moral education. It uses descriptive analytical method, in which the author refers to Sufi works that talk about moral education particularly al-Ḥikam. The findings are: first, the Sufi-style moral education is one of moral education methods focusing on self-empowerment and purification. It is hoped to get an improvement and even reach the level of gnosis (ma’rifat) which is in turn able to spread peace in this world. Second, Ibn Athoillah is the Sufis master who has a major role in the improvement of his pupils moral, especially through his work, al-Ḥikam. Third, his thought on Sufistic education can be applied in four stages: teaching, best practice, habituation, and strengthening. Keywords: Ibn ‘Aṭāillāh al-Sakandarī; moral education; al- Ḥikam; mysticism